2019
DOI: 10.21276/ijcmr.2019.6.11.19
|View full text |Cite
|
Sign up to set email alerts
|

Control of Shivering with Prophylactic Ketamine During Subarachnoid Block: A Placebo-Controlled Randomised Double- Blind Study

Abstract: Introduction: Shivering is a common and challenging side effect of anaesthesia and may result in different degrees of perioperative hypothermia. Hence, the aim of the study was to compare the efficacy of ketamine to prevent shivering during subarachnoid block inpatient undergoing elective surgery. Material and Methods: We conducted a prospective randomized, double-blind placebo-controlled trial with total of 90 ASA I and II patients of either sex between the ages of 18-60 years undergoing elective infra-umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The finding was similar to Seyam et al [16] and Zoengmawia et al [17] where only 14% of the patients had IOSH more than Grade 3 in ketamine group and none among the patients had IOSH more than Grade 3 in ketamine group respectively in either of the studies.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The finding was similar to Seyam et al [16] and Zoengmawia et al [17] where only 14% of the patients had IOSH more than Grade 3 in ketamine group and none among the patients had IOSH more than Grade 3 in ketamine group respectively in either of the studies.…”
Section: Resultssupporting
confidence: 89%
“…They found that the IOSH incidence was remarkably lesser in ketamine group (13.79%) when compared with its placebo (58.06%) in patients undergoing elective abdominal and lower limb surgeries under spinal anaesthesia (p<0.001). Seyam et al [16] and Zoengmawia et al [17] compared ketamine as a single IV bolus at a dose of 0.2 mg/kg compared with tramadol and ketamine in two different doses (0.25 mg/kg and 0.5 mg/kg), respectively, with placebo and concluded that the incidence of IOSH was much lesser in ketamine after SA (p<0.05). All these three studies were consistent with the results of this study and proved that the dose of 0.1 mg/kg of ketamine is also effective to control IOSH when compared with higher doses of ketamine as used in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Another research done at the institution civil hospital in Aizawl, Mizoram, found that ketamine significantly reduced core temperature compared to the control group. This may be because spinal anesthetics have a vasodilatory effect (33).…”
Section: Discussionmentioning
confidence: 99%